2022
DOI: 10.1038/s42003-022-03181-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-obligate pairwise metabolite cross-feeding suggests ammensalic interactions between Bacillus amyloliquefaciens and Aspergillus oryzae

Abstract: Bacterial-fungal metabolite trade-offs determine their ecological interactions. We designed a non-obligate pairwise metabolite cross-feeding (MCF) between Bacillus amyloliquefaciens and Aspergillus oryzae. Cross-feeding Aspergillus metabolites (MCF-1) affected higher growth and biofilm formation in Bacillus. LC-MS/MS-based multivariate analyses (MVA) showed variations in the endogenous metabolite profiles between the cross-fed and control Bacillus. We observed and validated that Aspergillus-derived oxylipins w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that microorganisms can interact in two models, namely nanowires and metabolites. To S. oneidensis , metabolite mediated interspecies communication was reported when it was mixed cultured with Klebsiella pneumoniae or Sideroxydans sp . CL21. , It was observed that there was nanowire formed when S. oneidensis MR-1 was supplemented to a denitrification system with P. denitrificans as denitrifiers .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that microorganisms can interact in two models, namely nanowires and metabolites. To S. oneidensis , metabolite mediated interspecies communication was reported when it was mixed cultured with Klebsiella pneumoniae or Sideroxydans sp . CL21. , It was observed that there was nanowire formed when S. oneidensis MR-1 was supplemented to a denitrification system with P. denitrificans as denitrifiers .…”
Section: Methodsmentioning
confidence: 99%